2017
DOI: 10.1107/s1600576717010494
|View full text |Cite
|
Sign up to set email alerts
|

Expected values and variances of Bragg peak intensities measured in a nanocrystalline powder diffraction experiment

Abstract: A rigorous study of sampling and intensity statistics applicable for a powder diffraction experiment as a function of crystallite size is presented. This analysis yields approximate equations for the expected value, variance and standard deviations for both the number of diffracting grains and the corresponding diffracted intensity for a given Bragg peak. The classical formalism published in 1948 by Alexander, Klug & Kummer [J. Appl. Phys. (1948), 19, 742-753] appears as a special case, limited to large crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The peak broadening of the dominant (110) reflex increased erratically from around 0.281° for the mirror like area to 0.421° for the P2000 area with a roughness of 187 nm as result of a grain refinement at the interface. A further increase of the roughness subsequently led to a smaller peak broadening of down to 0.319° (P500) following the behavior of the maximum peak intensity, as expected from their mutual relation [19]. In total, taking into account the finite X-ray penetration depth of several micrometers in our case, it can be concluded that the mechanically treated surfaces consist of a certain polycrystalline fraction, which is relevant, in particular, for the optical absorption during the laser polishing process, as well as for the field emission behavior.…”
Section: Sample Preparation and Characterisationmentioning
confidence: 71%
“…The peak broadening of the dominant (110) reflex increased erratically from around 0.281° for the mirror like area to 0.421° for the P2000 area with a roughness of 187 nm as result of a grain refinement at the interface. A further increase of the roughness subsequently led to a smaller peak broadening of down to 0.319° (P500) following the behavior of the maximum peak intensity, as expected from their mutual relation [19]. In total, taking into account the finite X-ray penetration depth of several micrometers in our case, it can be concluded that the mechanically treated surfaces consist of a certain polycrystalline fraction, which is relevant, in particular, for the optical absorption during the laser polishing process, as well as for the field emission behavior.…”
Section: Sample Preparation and Characterisationmentioning
confidence: 71%